Analysis of the Flexing Phenomenon "Mario Dandy Satriyo" in the Perspective of Islamic Communication Ethics - Ramadanti, Magfirah; Fatimah, Fatimah; Suhadi, Suhadi (Palakka : Media and Islamic Communication, 2025)
This research discusses the flexing phenomenon carried out by the son of official Mario Dandy Satriyo based on the perspective of Islamic communication ethics. This research aims to determine the ethical views of Islamic communication through 6 (six) qawlan on the flexing content of official Mario Dandy Satriyo's children on social media.The type of research used in this thesis is qualitative research, with library data collection techniques, namely observation and documentation, and analyzed using qualitative data analysis techniques proposed by Miles and Huberman.The results of this research show that the flexing phenomenon of Mario Dandy Satriyo who shows off his luxury vehicles on his social media platforms is contrary to the perspective of Islamic Communication Ethicsin 6 (six) forms or types of speaking styles (qawlan). The six qawlan (qawlan sadidan, qawlan baligha, qawlan ma'rufan, qawlan karima, and qawlan layyina) emphasize the importance of words or actions that are correct, effective, right on target, noble and gentle. This is in contrast to the flexing action to show off luxury vehicles carried out by Mario Dandy Satriyo.